Multiorgan transcriptomics in mice identifies immunoglobulin heavy constant mu ( Ighm ) as a tissue-level aging biomarker - Fan-Qian Yin; Xia-Yan Wang; Yong-Xuan Li; Kai-Jing Li; Si-Yu Ma; Meng-Jiao Lv; Zhen-Hua Liu; Wei-Xia Zhong; Yan Liu; Chuan-Fang Tang; Hong-Shi Liu; Yuze Li; et al. (Proceedings of the National Academy of Sciences, 2025)
Identifying aging-associated biomarkers applicable for multiple tissues is challenging but crucial for assessing tissue aging. Here, we obtained and analyzed 456 transcriptomes on 17 organs from 30 C57BL/6 J mice with different ages, revealing the consistently upregulated mRNAs of Ighm , C4b , and Ccl8 in most aged organs. This finding received support from independent transcriptomic and proteomic datasets and was further validated through western blot, enzyme-linked immunosorbent assay (ELISA), and immunofluorescence, arguing for both Ighm mRNA and protein as tissue-level aging biomarkers, at least in mice. Its sensitivity to antiaging interventions further emphasizes the significance of Ighm in assessing tissue aging in mice.